Pharmacogenomics: an update - Ingelman-Sundberg, Magnus (Henry Stewart Talks, 2023)
Individualized medicine, Human P450 genes, CYP2D genes, Pharmacogenetic biomarkers, Escitalopram pharmacokinetics, Genetic polymorphism, Drug development, Pre-emptive genotyping, Adverse drug reactions (ADRs), Missing heritability